Low-dissipation optimization of the prefrontal cortex in the −12° head-down tilt position: A functional near-infrared spectroscopy study - Lun, Tingting; Wang, Dexin; Li, Li; Zhou, Junliang; Zhao, Yunxuan; Chen, Yuecai; Yin, Xuntao; Ou, Shanxing; Yu, Jin; Song, Rong (Frontiers in Psychology, 2022)
Our present study set out to investigate the instant state of the prefrontal cortex (PFC) in healthy subjects before and after placement in the -12° head-down tilt (HDT) position in order to explore the mechanism behind the low-dissipation optimization state of the PFC. 40 young, right-handed healthy subjects (male: female = 20: 20) were enrolled in this study. Three resting state positions, 0° initial position, -12° HDT position, and 0° rest position were sequentially tested, each for 10 minutes. A continuous-wave functional near-infrared spectroscopy (fNIRS) instrument was used to assess the resting state hemodynamic data of the PFC. After preprocessing the hemodynamics data, we evaluated changes in resting-state functional connectivity (rsFC) level and beta values of PFC. The subjective visual analogue scale (VAS) was applied before and after the experiment. The presence of sleep changes or adverse reactions were also recorded. Pairwise comparisons of the concentrations of oxyhemoglobin (HbO), deoxyhemoglobin (HbR), and hemoglobin (HbT) revealed significant differences in the aforementioned positions. Specifically, the average rsFC of PFC showed a gradual increase throughout the whole process. In addition, based on graph theory, the topological properties of brain network, such as small-world network and nodal degree centrality were analyzed. The results show that global efficiency and small-world sigma (σ) value were differences between 0°initial and 0°rest. In this study, placement in the -12° HDT had a significant effect on PFC function, mainly manifested as self-inhibition, decreased concentration of HbO in the PFC, and improved rsFC, which may provide ideas to the understanding and explanation of neurological diseases.